Analisis Sifata Mekanis Beton SCC menggunakan Bahan Tambah Superplasticizer dengan Pemanfaatan Teknologi High Volume Fly Ash Concrete - Zein, Haqqu Fatih, Mochamad Solikin, S.T. M.T. Ph.D (2017)
Many difficulties execution casting in fields like concrete that's too thin, curved concretes, range between reinforcement Its too meeting, then the concrete experience of separation between Fine aggregate, cement, and water with plane coarse aggregate (segregation), by therefore concrete SCC (self-Compacting concrete) is required that concrete able to solidify itself. For a review fly ash which are the findings of coal combustion power plant then found High Technology Volume Fly Ash Concrete (HVFA) technology that fly ash content concrete by 50% or more cement substitute. This research is aims to review utilizing HVFA technology development with f'c SCC concrete of 25 MPa. This research is conducted using 50% Of fly ash cement weight, with fas (water cement ratio) value of 0.35 and superplasticizer 1.5% of cement weight. For a review test compressive strength on age 28 days and 56 days WITH A test specimen shaped cylinder with diameter of 15 cm and Height 30 cm, flexible strength on age 56 days with test object beam measuring 15 cm x 15 cm x 50 cm, and water absorption on age 56 days by diameter cylindrical test object 10 cm height 5 cm. Testing of the findings compressive strength average of SCC concrete cement with 100% amounting to 19.25 MPa findings on age 28 days and amounted to 24.91 MPa on age 56 days, while the SCC the concrete using fly ash 50% of compressive strength at 12, 08 MPa at age 28 days and 21.89 MPa on age 56 days. flexible strength value bending average of SCC concrete beams with 100% more high cement outcome compared using flexible strength with using of 50% SCC concrete beams with fly ash ,but the results can't be used as references because sometime there was an errors when testing concrete beams. The average value of water absorption SCC concrete without fly ash amounted to 2.95% and the average value of water absorption of concrete scc with the using of 50% fly ash is at 2.01%. Values of flexible strength and compressive strength with the use bending SCC concrete with 50% fly ash less than the SCC concrete using 100% of cement, concrete with 50% fly ash using SCC is less water absorption compared using 100% of cement.